Impact of interventions for adverse events by oncology pharmacists before versus after medical examination in outpatient chemotherapy: a retrospective, comparative study - Shinsaku Washinosu; Tatsuya Hayama; Akihiro Uchiike; Shinya Tsuboi; Katsuyuki Hazama; Sakae Fukushima; Kei Saito; Katsuhiro Miura (Journal of Pharmaceutical Health Care and Sciences, 2026)
Abstract Background While pharmacist interventions improve clinical outcomes in cancer treatment, their optimal timing remains unclear. To address psychological barriers to modifying prescriptions during conventional post-examination interventions, we shifted to a proactive, pre-examination approach. This study evaluated the impact of this proactive management on clinical outcomes in outpatients receiving chemotherapy. Methods We conducted a retrospective, comparative study of pharmacist interventions for chemotherapy-related adverse events at the Tumor Center of Nihon University Itabashi Hospital. Patients who received pharmacist interventions prior to their medical examinations between June 2024 and May 2025 (proactive intervention group) were compared with those who received interventions after their examinations between June 2023 and May 2024 (conventional intervention group). The major endpoints were the improvement rate (IR: the proportion of adverse events graded ≥ 2 at baseline that improved to grade ≤ 1) and the complete resolution rate (CRR: the proportion of adverse events of any grade at baseline that achieved complete symptom resolution). Results The proactive and conventional groups included 188 and 164 patients, with 303 and 227 interventions analyzed, respectively. At baseline, the proactive group had a significantly higher proportion of female patients, who were considered susceptible to chemotherapy-induced nausea and vomiting (CINV). Both the IR and the CRR were significantly higher in the proactive group (80% vs. 69%, P = 0.034, and 50% vs. 30%, P < 0.001, respectively). Sensitivity analyses accounting for this demographic imbalance confirmed that the proactive group achieved significantly higher IR and CRR for CINV (93% vs. 70%, P = 0.009, and 48% vs. 23%, P = 0.002, respectively). After excluding CINV, IRs were similar between the groups (74% vs. 68%, P = 0.356), but the CRR for other adverse events remained significantly higher in the proactive group (51% vs. 32%, P < 0.001). Conclusions Proactive, pre-examination pharmacist interventions were associated with earlier identification of lower-grade adverse events and a higher complete resolution rate of treatment-related toxicities compared to the conventional post-examination approach. Implementing this proactive framework may represent a critical step toward optimizing symptom management and the overall quality of outpatient cancer care.